Pengaruh Fasilitas dan Lokasi terhadap Kepuasan Konsumen : Survei pada Konsumen Z’dulur Coffee & Pool Kab. Tasikmalaya - Furi Marginani Lenggana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial effect of facilities and locations on customer satisfaction at Z'Dulur Coffee & Pool Tasikmalaya. The research method used in this study is a quantitative method with a survey approach. The population in this study amounted to 100 respondents. The sampling technique used was purposive sampling. The method used is multiple linear regression analysis with SPSS (Statictical Product and Service Solution) Version 25 application. The results of this study indicate that facilities and location simultaneously have a significant effect on customer satisfaction at Z'Dulur Coffee & Pool Tasikmalaya. Facilities partially have a significant effect on customer satisfaction at the Z'Dulur Coffee & Pool. Location, partially has a significant effect on customer satisfaction at Z'Dulur Coffee & Pool.